Numerical analysis on seismic resistance of a two-story timber-framed structure with stone and earth infill. Issue 6 (18th August 2019) - Fritsch, E.; Sieffert, Y.; Algusab, H.; Grange, S.; Garnier, P.; Daudeville, L.
ABSTRACT: Due to their seismic resistance, traditional timber-framed structures with masonry infill suffered little damage during recent earthquakes. Moreover, timber-framed structures can be built with reduced costs thanks to the use of locally available materials such as wood, stone, and earth. Based on an experimentally validated numerical simulation for a one-story house, the seismic resistance of a similar two-story house is investigated. A simplified Finite Element Model with linear and nonlinear truss elements is proposed to analyze the seismic resistance of a two-story building. Nonlinear hysteresis constitutive laws are defined only for two majorcomponents of the structure which are assumed to be representative of the global structure behavior: diagonal X-crosses (concentrating the interaction with the infill material) and steel strip connections. These kinds of structures have been overlooked due to a lack of knowledge of their potential behavior in seismic prone area and a lack of building codes and standards for their own design. To promote them, a failure criterion, that might easily be used in engineering studies, is required. This article proposes a simple criterion based on Eurocode 8 to quantify the seismic resistance of one- and two-story houses. The simulation shows that, even in case of high intensity ground motion, the two-story building should not be collapsed. This study may help at designing two-story timber-framed structures in seismic prone areas for (re)construction projects.